Concurrency testing using symbolic path finder - Kumar Sahoo, Bidush; Ray, Mitrabinda (International Journal of Engineering and Technology, 2018)
Concurrent programs have specific features such as italic communication, synchronization and nondeterministic behavior that make the testing activity complex. The objective is to find various types of concurrent defects. In this paper, we have used a model checking tool called Symbolic Path Finder (SPF) which is the upgradation of Java Path Finder (JPF) for concurrent testing. SPF is used for generating the test cases to check concurrent defects such as deadlock, race condition etc. SPF generates symbolic execution tree of the given code which is used as an input for test case generation. The execution is done for finding the test cases in concurrent program where number of threads is operating together with the concurrent defects. The test cases show the type of concurrent defects in the respective line number of the source code.Â Â